A hybrid protocol for the average consensus of multi-agent systems with impulse time window. Issue 7 (May 2020) - Hu, Xiang; Zhang, Zufan; Li, Chuandong; Zhang, Qiangqiang
Abstract: In this paper, a control protocol is proposed, which can make the states of multi-agent systems achieve average consensus over time. Periodicity is one of the characteristics of the control protocol, we divide each period of the control protocol into three parts, some continuous inputs for part 1, an impulse input with time window for part 2, and another continuous inputs for part 3. The system is called A hybrid protocol for the average consensus of multi-agent systems with impulse time window . We study the control protocol by constructing the Lyapunov function and mathematical induction method. We give a strict mathematical proof of the feasibility of the control protocol. At the end of this paper, we use a numerical example to simulate the control protocol, and the experimental results are excellent. Due to impulse time window is considered in each control protocol, the control protocol in this paper is closer to reality and can be better applied to industrial production, which makes the control protocol more practical and efficient.